Autoimmune Neutropenia Associated with Autoimmune Pancreatitis - Sato, Shuzo; Irisawa, Atushi; Sato, Ai; Shibukawa, Goro; Suzuki, Rei; Takagi, Tadayuki; Ikeda, Tsunehiko; Sato, Masaki; Hikichi, Takuto; Obara, Katsutoshi; et al. (JOP. Journal of the Pancreas, 2011)
Context We report a rare case of autoimmune neutropenia associated with autoimmune pancreatitis. Case report A 61-year-old man was referred to our hospital with slight epigastralgia. He had been admitted to another hospital with exacerbation of diabetes and jaundice. Blood tests showed low white blood cell and neutrophil counts (1,800 µL-1 and 3%, respectively), and elevated transaminase, biliary enzyme, amylase and lipase levels. Serum IgG and IgG4 levels were elevated to 2,693 mg/dL and 454 mg/dL, respectively. Abdominal CT showed diffuse pancreatic swelling, and MRCP revealed diffuse narrowing of the main pancreatic duct and dilation of the common bile duct. An additional EUS-FNA was performed in our hospital. Laboratory data, imaging and histopathological findings confirmed the diagnosis of autoimmune pancreatitis. However, the low white blood cell count continued. For additional investigation, a bone marrow examination was performed, indicating a granulocyte maturation disorder. Moreover, anti-neutrophil antibodies were positive. Therefore, a diagnosis of autoimmune neutropenia associated with autoimmune pancreatitis was made. After steroid therapy, the anti-neutrophil antibodies disappeared and the white blood cell count was within the reference limit. No recurrence of disease has been observed since then. Conclusion Autoimmune neutropenia, which is positive for anti-neutrophil antibodies, can be associated with autoimmune pancreatitis. Image: Clinical course.